ANALISIS DETERMINAN NILAI PERUSAHAAN: STUDI PADA EMITEN LQ45 DI BURSA EFEK INDONESIA - Hasma, Hasma; Sudirman, Nengsi (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to test independent variables including the effect of profitability, leverage, and company size on company value. This study is a quantitative study with an associative approach. This study uses a sample of financial statements of LQ 45 index companies listed on the Indonesia Stock Exchange for the period 2020-2024. Based on the purposive sampling method, the number of companies sampled in this study was 16 companies out of 45 companies with observations for 5 years. Hypothesis testing in this study uses multiple regression techniques using the Statistical Package for the Social Science (SPSS) version 26 program. The results of this study indicate that profitability, leverage and company size have a simultaneous and significant effect on company value. Partially, profitability and leverage have a positive and significant effect on company value. While company size does not affect company value. Simultaneously, profitability, leverage and company size have a significant and significant effect on company value.